Manajemen Kebidanan Berkesinambungan : Studi Kasus Pada Ibu Dengan Asuhan Komprehensif - Sri Dewi Haryati; Desi Ernita Amru (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Indicators to measure the quality of health services in an area can be seen from the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). One of the ways that can be done to reduce maternal mortality (MMR) and infant mortality (IMR) is by implementing continuous care. The purpose of this continuous midwifery care is to be able to provide comprehensive midwifery care to Mrs.